Housing tenure and wealth distribution in life-cycle economies - Pedro Silos (Federal Reserve Bank of Atlanta, 2005)
Common practice in the housing and wealth distribution literature has proceeded as if the modeling of housing rental markets was unnecessary due to renters' relative low levels of wealth and the small fraction they represent in the total population. This paper shows, however, that their inclusion matters substantially when dealing with wealth concentration over the life cycle. Renters are concentrated in the poorer and younger groups. This concentration results in a pattern of housing wealth concentration over an agent's life that is decreasing, with a slope as steep as that of nonhousing (or financial) wealth. The author constructs an overlapping-generations economy with a housing rental market that is consistent with this fact.
Keywords: 330; Besitzformwahl; Vermögensverteilung; Lebenszyklus; Overlapping Generations; Theorie; USA